2009
DOI: 10.1007/s12633-009-9011-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hydrophilicity from Poly(ethylene glycol) in Amphiphilic Conetworks with Poly(dimethylsiloxane)

Abstract: This paper focuses on the improvement of hydrophicility and water content of poly(dimethylsiloxane) (PDMS) by bonding a hydrophilic macromer, hydroxyl-terminated linear poly(ethylene glycol) (PEG), into a highly hydrophobic macromer, hydroxyl-terminated linear PDMS to prepare amphiphilic conetworks (APCNs) with the crosslinkers, tetraethoxysilane (TEOS) and bis [(3-methyldimethoxysilyl) propyl]-polypropylene oxide (BMPPO), which also functioned as a compatibilizer. Fourier transform infrared results clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…For PEG 1000 concentrations above 30% (i.e., H35L35P30 and H30L30P40), no significant difference ( p > 0.05) in contact angle was observed. Lin et al 56 also reported that increasing the proportion of PEG in amphiphilic co-networks of poly(dimethylsiloxane) resulted in a reduction in their contact angle with deionized water up until a maximum PEG ratio of 6/1. After this point, contact angle remained constant.…”
Section: Resultsmentioning
confidence: 99%
“…For PEG 1000 concentrations above 30% (i.e., H35L35P30 and H30L30P40), no significant difference ( p > 0.05) in contact angle was observed. Lin et al 56 also reported that increasing the proportion of PEG in amphiphilic co-networks of poly(dimethylsiloxane) resulted in a reduction in their contact angle with deionized water up until a maximum PEG ratio of 6/1. After this point, contact angle remained constant.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophilicity of various polymer blends was measured in terms of contact angle as shown in Figure 4. The static contact angle of virgin PS was found to be 80 °, and increasing the concentration of PEG, the contact angle was decreased [25]. The PSP5 blend with 5% PEG concentration has demonstrated contact angle of 66 ° [26].…”
Section: Contact Angle and Surfacementioning
confidence: 91%
“…The morphologies of the x(PEG/PPG:PDMS:Ad) membranes were observed using field emission scanning electron microscopy (FE-SEM); further, their surfaces were also examined ( Figure 7 ). As can be seen in the images, sphere-shaped phases were dotted over the entire surface for the x(10:0.75:0.25) and x(10:0.5:0.5) membranes, possibly because phase separation occurred between the hydrophilic region, owing to PEG, and the hydrophobic region, owing to the PDMS structure ( Figure 7 a,b, respectively) [ 22 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The morphologies of the x(PEG/PPG:PDMS:Ad) membranes were observed using field emission scanning electron microscopy (FE-SEM); further, their surfaces were also examined (Figure 7). As can be seen in the images, sphere-shaped phases were dotted over the entire surface for the x(10:0.75:0.25) and x(10:0.5:0.5) membranes, possibly because phase separation occurred between the hydrophilic region, owing to PEG, and the hydrophobic region, owing to the PDMS structure (Figure 7a,b, respectively) [22,40]. To determine which precursor of the three components (PEG/PPG, PDMS, and adamantane), caused the sphere-shaped phases, energy dispersive spectroscopy (EDS) mapping was performed to investigate the distribution of elements and their relative content (atomic %), as shown in Figure 8 and Table 2.…”
Section: Morphological Analysis Of the X(peg/ppg:pdms:ad) Membranesmentioning
confidence: 93%
See 1 more Smart Citation